Positivity effect in source attributions of arousal-matched emotional and non-emotional words during item-based directed forgetting - Gallant, Sara N.; Yang, Lixia (Frontiers in Psychology, 2014)
Consistent with their emphasis on emotional goals, older adults often exhibit a positivity bias in attention and memory relative to their young counterparts (i.e., a positivity effect). The current study sought to determine how this age-related positivity effect would impact intentional forgetting of emotional words, a process critical to efficient operation of memory. Using an item-based directed forgetting task, 36 young and 36 older adults studied a series of arousal-equivalent words that varied in valence (i.e., positive, negative, and neutral). Each word was followed by a cue to either remember or forget the word. A subsequent “tagging” recognition task required classification of items as to-be-remembered (TBR), to-be-forgotten (TBF), or new as a measure of directed forgetting and source attribution in participants’ memory. Valence did not affect intentional forgetting in both young and older age groups. A goal-consistent valence effect did, however, emerge in older adults’ source attribution performance. Specifically, older adults assigned more TBR-cues to positive words and more TBF-cues to negative words. Results are discussed in light of existing literature on emotion and directed forgetting as well as the socioemotional selectivity theory underlying the age-related positivity effect.